Alterations in insulin‐like growth factor system in spinal muscular atrophy. Issue 5 (15th September 2022) - Kaymaz, Ayse Yesbek; Bal, Sevgi Kostel; Bora, Gamze; Talim, Beril; Ozon, Alev; Alikasifoglu, Ayfer; Topaloglu, Haluk; Yurter, Hayat Erdem
Abstract: Introduction/Aims: Spinal muscular atrophy (SMA) is an inherited neuromuscular disease caused by survival motor neuron (SMN) protein deficiency. Insulin‐like growth factor‐I (IGF‐I) is a myotrophic and neurotrophic factor that has been reported to be dysregulated in in vivo SMA model systems. However, detailed analyses of the IGF‐I system in SMA patients are missing. In this study, we analyzed the components of the IGF‐I system in serum and archived skeletal muscle biopsies of SMA patients. Methods: Serum IGF‐I, IGF binding protein (IGFBP)‐3, and IGFBP‐5 levels were analyzed in 11 SMA patients and 13 healthy children by immunoradiometric and enzyme‐linked immunosorbent assays. The expression of IGF‐I, IGF‐I receptor, and IGFBP‐5 proteins was investigated by immunofluorescence analysis in the archived skeletal muscle biopsies of nine SMA patients, six patients with non‐SMA‐related neuromuscular disease and atrophic fibers in muscle biopsy, and four controls. Results: A significant decrease in IGF‐I levels (mean ± SD: −1.39 ± 1.46 vs. 0.017 ± 0.83, p  = .02) and increase in IGFBP‐5 levels (mean ± SD: 2358.5 ± 1617.4 ng/mL vs. 1003.4 ± 274.3 ng/mL, p  = .03) were detected in serum samples of SMA patients compared to healthy controls. Increased expression of IGF‐I, IGF‐I receptor, and IGFBP‐5 was detected in skeletal muscle biopsies of SMA patients and non‐SMA neuromuscular diseases, indicating atrophy‐specific alterations in the pathway. Discussion: Our findings suggested that the components of the IGF‐I system are altered in SMA patients at both the systemic and tissue‐specific levels.